SIFAT PENYERAPAN BAHAN PENGAWET PADA BEBERAPA JENIS KAYU BANGUNAN - Kusumaningsih, Karti Rahayu (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Wood preservation is important to increase the service life of species woods which have low natural durability. The absorption of preservative in wood is effected by anatomy, physical and chemical properties of wood and kind of preservative. The purpose of this research is to know effect of wood species, i.e : Paraserianthes falcataria, Shorea spp., Cocos nucifera and Toona sureni, and kind of preservative namely borax (Na2B4O7.5H2O) and terusi (CuSO4) on the absorption, retention and penetration of preservative. Results of this research showed that wood species investigated gived significant effect on the absorption and retention. The highest absorption was resulted on Paraserianthes falcataria and the highest retention was resulted on Cocos nucifera wood. Borax gived higher absorption, retention and penetration than terusi. Paraserianthes falcataria wood tend to easier to absorb preservative than three wood others. Key Words : Preservative, Absorption, Retention, Penetration